Staatsfundamentalnorm (Pancasila) Sebagai Bahan Pembaruan Sistem Hukum Di Indonesia - Redyanto Sidi; Hasan Basri; Ahmad Akbar; Irhamuddin Irhamuddin; Nirmayana Sinaga (Iuris Studia: Jurnal Kajian Hukum, 2021)
Pancasila is the ideology and way of life of the Indonesian people which provides the basis for philosophy and values for all of us. The placement of Pancasila as the source of all sources of state law is in accordance with the Preamble to the 1945 Constitution of the Republic of Indonesia in the fourth paragraph, namely Belief in One Supreme God, just and civilized humanity, Indonesian Unity, Democracy led by wisdom in Deliberation/Representation, and Social justice for all Indonesian people. Placing Pancasila as the basis and ideology of the state as well as the philosophical basis of the state so that any material contained in laws and regulations must not conflict with the values contained in Pancasila